Giant energy-storage density with ultrahigh efficiency in lead-free relaxors via high-entropy design - Chen, Liang; Deng, Shiqing; Liu, Hui; Wu, Jie; Qi, He; Chen, Jun (Nature communications, 2022)
Next-generation advanced high/pulsed power capacitors rely heavily on dielectric ceramics with high energy storage performance. However, thus far, the huge challenge of realizing ultrahigh recoverable energy storage density ( W rec ) accompanied by ultrahigh efficiency ( η ) still existed and has become a key bottleneck restricting the development of dielectric materials in cutting-edge energy storage applications. Here, we propose a high-entropy strategy to design “local polymorphic distortion” including rhombohedral-orthorhombic-tetragonal-cubic multiphase nanoclusters and random oxygen octahedral tilt, resulting in ultrasmall polar nanoregions, an enhanced breakdown electric field, and delayed polarization saturation. A giant W rec ~10.06 J cm −3 is realized in lead-free relaxor ferroelectrics, especially with an ultrahigh η ~90.8%, showing breakthrough progress in the comprehensive energy storage performance for lead-free bulk ceramics. This work opens up an effective avenue to design dielectric materials with ultrahigh comprehensive energy storage performance to meet the demanding requirements of advanced energy storage applications. Dielectric ceramics are widely used in advanced high/pulsed power capacitors. Here, the authors propose a high-entropy strategy to design “local polymorphic distortion” in lead-free ceramics, achieving high energy storage performance.